2002
DOI: 10.1177/002242780203900103
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Predictors of Offense Trajectories

Abstract: Previous research has shown heterogeneity in offense trajectories. Using data from the Seattle Social Development Project, a longitudinal study of 808 youths followed since 1985, this study seeks to identify childhood predictors of different offense trajectories. Five offense trajectories were identified using semiparametric, group-based modeling: nonoffenders, late onsetters, desisters, escalators, and chronic offenders. Multinomial logistic regressions were then employed to examine childhood predictors measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 47 publications
10
135
0
7
Order By: Relevance
“…Despite support for a distinction based on the age of onset of ASB, it is important to note that some studies did not find both childhood and adolescent onset patterns paths (Chung et al 2002;Fergusson et al 2000;Wiesner and Capaldi 2003). One possible explanation of these contradictory results may be a methodological artefact that we refer to as 'lumping or splitting' (see Vitaro et al 2006).…”
mentioning
confidence: 80%
“…Despite support for a distinction based on the age of onset of ASB, it is important to note that some studies did not find both childhood and adolescent onset patterns paths (Chung et al 2002;Fergusson et al 2000;Wiesner and Capaldi 2003). One possible explanation of these contradictory results may be a methodological artefact that we refer to as 'lumping or splitting' (see Vitaro et al 2006).…”
mentioning
confidence: 80%
“…Studies using official records have identified a group with an adult-onset offending pattern [13,48], but evidence is mixed using self-report data. Several studies using population-based samples have identified a late-onset trajectory of offenders whose antisocial behavior starts to accelerate from very low to higher levels in their late teens [7,9], but others have failed to reveal such a pattern [4,45]. There are two explanations of adult-onset criminality.…”
Section: Introduction Developmental Trajectories Of Antisocial Behavimentioning
confidence: 99%
“…La presencia de comportamientos agresivos altera el desempeño académico de niños y niñas ya que, por presentarlos, los niños pueden ser excluidos de los procesos educativos en sus escuelas (14,15) . La exclusión del aula está asociada a que se manifiesten de manera más clara y frecuente actitudes hostiles y violentas frente a las demás personas en el entorno social y familiar del menor.…”
Section: Discussionunclassified